Analisis Penerapan Kebijakan Peningkatan Fasilitas Rawat Inap Bagi Pegawai dan Keluarganya Serta Dampaknya Terhadap Loyalitas dan Respon Positif Pegawairumah Sakit Balimed Buleleng - Wayan Adhi Suryana; Deni Iskandar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the implementation of the inpatient facility improvement policy for employees and their families at BaliMed Buleleng Hospital, as well as its impact on employee’s loyalty and positive responses. The main focus is to explore how the policy influences employee’s loyalty, including commitment, willingness to stay, and readiness to make sacrifices for the hospital, along with employee’s responses such as job satisfaction and work motivation. This research is a qualitative descriptive study, and its data was collected through questionnaires and direct observation. The objects of the study are employee’s loyalty and response, meanwhile the subjects are the employees of BaliMed Buleleng Hospital who have utilized the improved inpatient facilities. Questionnaire data were used to gather employee’s perceptions, while observation was conducted to complement and validate the data directly. The results show that the implementation of improved inpatient facilities for employees and their families has a positive impact on increasing employee loyalty at BaliMed Buleleng Hospital. Moreover, the implementation of this policy also improves employee’s responses at work. Employee’s responses became significantly more positive after the policy was implemented.